Revitalisasi Nilai Al-Qur'an dan Hadits dalam Pembentukan Etos Kerja, Profesionalisme, Spiritualitas, Inovasi, Keseimbangan Sosial, dan Keberlanjutan Muslim Modern - Sus Shalawati; Ainur Rofiq Sofa (Jurnal Budi Pekerti Agama Islam, 2025)
This article examines the role of the values of the Qur'an and Hadith in shaping a work ethic relevant to the challenges of the modern era. Using a multidimensional approach, this paper explores how the integration of Islamic teachings can strengthen professionalism, spirituality, innovation, social balance, and sustainability in the life of a Muslim in the workforce. The study focuses on the revitalization of fundamental Islamic values that emphasize the importance of hard work (Ijtihad), trustworthiness, integrity, and justice as the foundation of a productive work ethic. Additionally, this study highlights how these values can inspire innovation and strengthen the balance between worldly and spiritual life (dunya and akhirah) in an era characterized by rapid change and numerous challenges. By linking Islamic principles with the professional needs of the global context, this article offers a new perspective on the relevance of religious teachings in supporting individual and organizational success, while also fostering social harmony within modern Muslim societies.